Effects of feeder design, gender, and dietary concentration of dried distillers grains with solubles on the growth performance and carcass characteristics of growing-finishing pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 2 × 2 × 2 factorial experiment was conducted to evaluate the interactive effects of feeder design (conventional dry vs. wet-dry feeder), gender (barrow vs. gilt), and dietary concentration of dried distillers grains with solubles (DDGS; 20% vs. 60%) on finishing pig performance. A total of 1,080 pigs (PIC 337 × 1050) were used in the 99-d experiment. Pigs were sorted by gender (barrows and gilts) into groups of 27, weighed (77.4 lb initial BW), allotted to pens containing 1 of the 2 feeder types, and assigned to a corn-soybean meal-DDGS-based feeding program of either 20% or 60% DDGS. A completely randomized design was used to evaluate the 8 treatment combinations, with 5 pens per treatment. This provided 20 pens per treatment for each of the three main effects (feeder type, gender, and DDGS concentration). All pigs were fed their assigned level of DDGS in 3 dietary phases (d 0 to 28, 28 to 56, and 56 to 78). On d 78, 2 pigs per pen were weighed and harvested. Jowl fat samples were collected from these pigs for fatty acid analysis and iodine value (IV). All remaining pigs were fed a common diet from d 78 to 99 that contained 20% DDGS and 4.5 g/ton of ractopamine HCl (Paylean; Elanco Animal Health, Indianapolis, IN). On d 99, all remaining pigs were harvested and carcass data were obtained from 885 pigs. Jowl fat samples were collected from 2 pigs per pen for fatty acid analysis and IV. Overall (d 0 to 99), pigs using the wet-dry feeder had greater (P < 0.001) ADG, ADFI, F/G, final BW, feed cost per pig, HCW, and backfat depth but decreased (P < 0.05) fat-free lean, jowl fat IV, premium per pig, value per cwt live, and net income per pig. Feeding 60% DDGS from d 0 to 78 resulted in decreased (P < 0.02) ADG, final BW, feed cost per pig, HCW, and backfat depth but increased (P < 0.05) F/G, fat-free lean, jowl fat IV, and net income per pig. Barrows had greater (P < 0.01) ADG, ADFI, F/G, final BW, feed cost per pig, HCW, and backfat depth but reduced fat-free lean, jowl fat IV, premium per pig, value per cwt live, and net income per pig. In conclusion, the greatest net income per pig resulted from feeding gilts 60% DDGS from d 0 to 78 and 20% DDGS with Paylean from d 78 to 99 using a conventional dry feeder. However, using wet-dry feeders improved ADG and ADFI of growing-finishing pigs and may improve the performance of slower growing populations within a group (e.g., gilts). Wet-dry feeders may also restore the growth rates of pigs fed adverse levels of DDGS. More research with wet-dry feeders is needed to resolve concerns with F/G, carcass leanness, and economic returns.
Keywords: Dried distillers grains with solubles; Feeders; Swine